Risk factors for the formation of gastroesophageal reflux disease and erosive lesions of the esophagus in adolescents - Г.В. Бекетова; О.О. Мощич (Zdorovʹe Rebenka)
Background. Gastroesophageal reflux disease (GERD) is a common chronic relapsing disease of the upper digestive tract, both among adults and children and adolescents. Among the adult population, this disease is most often detected in people older than 60, while in children, a significant increase in its prevalence is noted with age, with a maximum in adolescents. GERD is characterized by a long-term course, polymorphism of clinical (esophageal and extraesophageal) manifestations, often subtle (which causes patients to seek medical help late), and can lead to the development of severe complications (erosive-ulcerative reflux esophagitis, Barrett’s esophagus, adenocarcinoma) and even sudden death in children. Therefore, it is important to identify risk factors (RF) for the development of GERD and destructive lesions of the esophagus in order to timely diagnose the disease and improve the effectiveness of its treatment. The authors provide up-to-date data on the RF for GERD in adults and children. However, in available scientific literature, there is practically no information on statistically significant combinations of RF for both GERD and destructive lesions of the esophageal mucosa in adolescents, which determined the need to conduct this study. The purpose was to find out the statistically significant RF for GERD and destructive lesions of the esophageal mucosa in adolescents and to develop the corresponding prognostic mathematical models. Materials and methods. To identify RF for GERD, a survey of 106 schoolchildren aged 15–17 and 81 adolescents suffering from GERD was conducted using a questionnaire developed by authors, pre-verified and adapted for the pediatric cohort, which included 68 questions (socio-psychological, socio-economic, socio-hygienic and biological). The diagnosis of GERD was verified according to the 2015 international NICE guidelines “Gastro-oesophageal reflux disease in children and young people: diagnosis and management”, updated 2019; the diagnosis of reflux esophagitis — according to the Los Angeles classification system. Prognostic mathematical models were created using correlation-regression, univariate and multivariate analysis, stepwise discriminant and Fisher’s discriminant analysis. Statistical processing was carried out using generally accepted methods of medical statistics. Results. The main statistically significant combinations of RF for GERD were burdened family history, pathology of the gastroduodenal zone, sliding hiatal hernia, obesity, chronic stress, smoking/alcohol consumption. For destructive lesions of the esophagus, such RF were as follows: burdened GERD family history, recurrent oral herpes, neurological disorders, obesity, sliding hiatal hernia, chronic stress. Given statistically significant RFs, corresponding prognostic mathematical models were created, and examples of their practical use were provided. Conclusions. The clarified RFs made it possible to create appropriate prognostic mathematical models that have sufficiently high sensitivity and specificity, positive and negative prognostic value and can be used in the practice of pediatricians, family doctors and pediatric gastroenterologists.